MENCARI FORMAT MODEL ORGANISASI YANG TEPAT UNTUK PESANTREN - Muhammad Fathurrahman, Ima Fitriyah dan (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Pesantren is the oldest Islamic education in Indonesia and attracts a large number of researches. Given that it hasÃ‚Â developed and transformed itself into various types, generalization is almost impossible to be made. PesantrenÃ‚Â is a unique educational institution and organization. This article attempts to examine the organizational modelÃ‚Â of the pesantren with a focus on its dictintive character. It argued that pesantren is based on a holistic modeÃ‚Â of organizational system, which is Ã¢â‚¬ËœbarÃ„ÂkahÃ¢â‚¬â„¢. The Ã¢â‚¬ËœbarÃ„ÂkahÃ¢â‚¬â„¢ or Ã¢â‚¬Ëœngalap barÃ„ÂkahÃ¢â‚¬â„¢ is an open system that is whatÃ‚Â distinguishes pesantren from other educational institutions in general. This article also addresses the questionÃ‚Â on what kind of organizational format that may be best implemented in pesantren.Keywords: Pesantren, BarÃ„Âkah, Organisasi